EXAMINATION OF EFFECTS OF ARTISTIC GYMNASTICS ON FLEXIBILITY OF 3TH & 4TH GRADE PUPILS OF ELEMENTARY SCHOOLS - Vesko Milenković; Dragana Aleksić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
In this work, the subject of the research is only one segment of the anthropological area, which refers to the appearance of appropriate motor abilities- flexibility. Flexibility is responsible to perform a movement to get her whit other motor abilities. It appears like ability to perform a movement with maximum amplitude. It is conditional with bone- joint system, it is a backward area of human body. The appropriate level of flexibility is necessary during each motor activity. Size and character of flexibility depend mostly on a kind of activity and on forms of the specific ability demonstration, when specific branch or discipline is concerned. The battery for the evaluation of flexibility consists of the following tests: MDPK, MISK, MBŠP. During the 2005/06 academic year, a research was conducted so as to determine the effects of current program of physical education teaching on motor abilities flexibility of female pupils. The research involved a total sample of 107 girls from the 3th and 4th grade of elementary school. The subjects were classified in experimental and control groups. The experimental group was made of 59 students and they were practicing according to planning instruction where the artistic gymnastics had the primary part. The control group of 48 students was practicing according to official instructional plan and program for P.E. of the Republic of Serbia. At the beginning of the academic year, initial (first) measurement was performed, followed by experimental final (second) measurement at the end of experiment. Research data was processed using SPSS standard statistics procedure. The multi-variant procedures were used in this research ant those were: the multi-variant analysis of the variable (MANOVA) and the discriminative analysis. Also, the mono-variant procedures were used and those were: the variable analysis (ANOVA) and the interval of entrust. After the experimental treatment, i.e. at the final testing, significant differences were found with female pupils in experimental and control groups concerning the all tests for the evaluation of flexibility. The basic conclusion is that the female pupils of experimental group achieved significantly higher teaching effects than the control group, in view of partly increased motor abilities, being the result of the effects of the experimental treatment, as well as other external and internal factors.